Incidence and patterns of abnormal corpus callosum in fetuses with isolated spina bifida aperta. (8th April 2021) - Kunpalin, Yada; Deprest, Jan; Papastefanou, Ioannis; Bredaki, Emma; Sacco, Adalina; Russo, Francesca; Richter, Jute; Jansen, Katrien; Ourselin, Sebastien; De Coppi, Paolo; David, Anna L.; Ushakov, Fred; et al.
Abstract: Objective: To determine the incidence and characterise corpus callosum (CC) abnormalities in fetuses with spina bifida aperta (SBA) between 18 and 26 weeks of gestation. Methods: This was a retrospective study on fetuses with isolated SBA and who were assessed for fetal surgery. Digitally stored ultrasound images of the brain were reviewed for the presence/absence of the CC, and the length and diameter of its constituent parts (rostrum, genu, body and splenium). We used regression analysis to determine the relationship between CC abnormalities and gestational age, head circumference, ventricle size, lesion level and lesion type. Results: Nearly three‐quarters of fetuses with isolated SBA had an abnormal CC (71.7%, 76/106). Partial agenesis was most common in the splenium (18.9%, 20/106) and the rostrum (13.2%, 14/106). The most common abnormal pattern was of a short CC with normal diameter throughout. Of note, 20.8% (22/106) had a hypoplastic genu and 28.3% (30/106) had a thick body part. Larger lateral ventricle size was associated with partial agenesis of the CC (odds ratio [OR]: 0.14, p  < 0.001) and inversely associated with a shorter CC (OR: 2.60, p  < 0.01). Conclusion: An abnormal CC is common in fetuses with isolated SBA who are referred for fetal surgery. Key Points: What's already known about this topic? In children with spina bifida aperta (SBA), the corpus callosum (CC) is often abnormal. CC abnormalities have a functional impact on children's cognitive function, language and social skills. The CC is fully developed and can be visualised by prenatal ultrasound at approximately 16 weeks' gestation. What does this study add? In three out of four fetuses with isolated SBA who are referred for fetal surgery assessment, the CC is structurally abnormal.